Production of Low-Fat Camel Milk Functional Ice creams Fortified with Camel Milk Casein and its Antioxidant Hydrolysates - Hajian, Nasim; Salami, Maryam; Mohammadian, Mehdi; Moghadam, Maryam; Emam-Djomeh, Zahra (Applied Food Biotechnology, 2020)
Background and objective: The objective of this study was to produce functional low-fat camel milk ice creams enriched with native camel milk casein or its antioxidant hydrolysates produced by chymotrypsin. Material and methods: Native or hydrolyzed camel milk caseins (0, 2 and 4%) were added to camel milk low-fat ice creams. Hydrolysates were characterized for molecular weights and antioxidant activities. Physical (hardness, overrun and melting resistance) and sensorial attributes of the final products were assessed. Results and conclusion: Results showed that the chymotrypsin-mediated hydrolysis significantly (P<0.05) increased 2,2′-azinobis (3-ethylbenzthiazoline-6-sulfonic acid) radical scavenging activity of the native camel milk casein. Apparent viscosity and consistency coefficient of the ice creams were increased by addition of proteins and hydrolysates due to their water holding capacity. Protein/hydrolysates-fortified samples showed higher melting resistances but lower overruns and softer textures, compared to control ice creams with no added native or hydrolyzed camel milk casein. Sensory analysis showed that only samples enriched with 2% of casein hydrolysate included sensory properties similar to those of control camel milk low-fat ice creams and other samples received lower sensory scores. Generally, this study has suggested that camel milk can be used to produce low-fat ice creams. Properties of these ice creams can be modified by adding various concentrations of native and hydrolyzed camel milk caseins. Conflict of interest: The authors declare no conflict of interest.